SUPPLY CHAIN ANALYSIS OF RICE MARKETING ACTORS IN DUMAI CITY IN SUPPORTING URBAN FOOD SECURITY - Septya, Fanny; Andriani, Yulia; Pebrian, Sispa; Yulida, Roza; Rosnita, Rosnita (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
Dumai City is a significant economic hub in Riau Province and a vital location for food distribution. Although it's an urban area, there is still a small amount of rice produced in Dumai City. However, most of the rice supply comes from various suppliers outside the region to meet the high demand. Due to this diverse supply chain, this study aims to analyze the structure, mechanisms, and performance of the marketing in the premium rice supply chain at each level of the marketing institution. This research was conducted using a survey method among marketing actors at each level of marketing institutions selected purposively. To analyze the structure and mechanism of the rice supply chain, qualitative analysis is used. Quantitative analysis is used to analyze marketing performance in the rice supply chain. The research method used was a survey of rice marketing institutions in Dumai City, utilizing both qualitative and quantitative analysis methods. The results show that three marketing institutions are involved in marketing rice in Dumai City, each with a unique supply chain. Upon analyzing the marketing performance of the premium rice supply chain, it was found that all marketing channels utilized by wholesalers and retailers are efficient. Among these channels, channel 3, supplier-wholesaler-end consumer, has the smallest margin value, while channel 2, out-of-town distributor-traditional retailer-end consumer, has the highest profit-cost ratio value of 125.67. This marketing channel offers the lowest price for premium rice at the end consumer level, thereby ensuring greater access to food for the community and promoting urban food resilience. Among these channels, channel 2 of retailers that were out-of-town distributor-traditional retailer-end consumers had the best marketing efficiency value (0,09%) and the highest profit-cost ratio value of 125.67. Based on the results of this research, it is a challenge for the development of local rice agro-industry in creating efficient marketing performance to strengthen regional food security.